1994
DOI: 10.1037/0893-164x.8.1.24
|View full text |Cite
|
Sign up to set email alerts
|

The relation between meaning in life and the occurrence of drug abuse: A retrospective study.

Abstract: Humans have been using plant-derived drugs for as long as they have recorded history. The purpose of this article was to assess the relation between meaning in life and drug abuse. An epidemiological, retrospective study was performed to compare personal meaning in life between a group of 49 individuals receiving inpatient treatment for drug abuse and a group of 49 matched, non-drug-abusing controls. Study participants in both groups completed the Purpose in Life Test and Life Attitude Profile-Revised. With bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(40 citation statements)
references
References 5 publications
(5 reference statements)
2
36
0
1
Order By: Relevance
“…For example, meaning in life was negatively associated with health drug use [25,26], heavy drinking [27], sedative use [28], and positively associated with health enhancing behaviors, such as physical activity [29] and diet control [30]. Although it has been established only in an adult population, meaning in life was also related to less smoking [31].…”
Section: Introductionmentioning
confidence: 96%
“…For example, meaning in life was negatively associated with health drug use [25,26], heavy drinking [27], sedative use [28], and positively associated with health enhancing behaviors, such as physical activity [29] and diet control [30]. Although it has been established only in an adult population, meaning in life was also related to less smoking [31].…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the more search for meaning in life increases (Steger, Mann, Michels & Cooper, 2009) the more anxiety, depression level and health risking behaviors increase (Marco et al, 2015), and level of psychological and pysical well being decreases (Steger et al, 2006;Steger et al, 2009). Meaning in life reported by individuals addicted to smoking, substance, alcohol, and drugs is found to be lower compared to those not addicted to such (Nicholson et al, 1994;Thege, Urban & Kopp, 2013;Waisberg & Porter, 1994) and meaning in life plays a facilitating role in psychotherapy (Debats, 1996). Furthermore, positive relationship between the Internet addiction and stressful life events (Whang et al, 2003), family problems (Lam, Peng, Mai & Jing, 2009), psychological traumas (Dalbudak, Evren, Aldemir & Evren, 2014), and academic problems (İskender & Akın, 2010;Odacı, 2011) gives the idea that problematic Internet use can be considered as a problem of meaning in life.…”
Section: Meaning In Life and Problematic Internet Usementioning
confidence: 83%
“…The measure has been used in numerous studies and found to be a valid and reliable instrument (Crumbaugh & Maholick, 1964, 1969Chamberlain & Zika, 1988;Zika & Chamberlain, 1992;Reker, 1977;Melton & Schulenberg, 2008). Researchers using the PIL test have found relatively low senses of life purpose among high school students involved in the use of narcotics (Padelford, 1974), prison inmates (Reker, 1977), apathetic college students (Coffienld, 1981 ), patients with psychopathological syndromes (Gonsalvez & Gon, 1983), drug addicts (Nicholson, et al, 1994), college students with anger issues (Sappington & Kelly, 1995), adolescent children of Bangladeshi divorcees (Rahman, 2004); and college students who engage in isolating verses interpersonal activities (Molasso, 2006). Positive correlations have been reported between the PIL test measures and psychological well-being among Chinese college students (Shek, 1993), self-efficacy among college students (DeWitz, 2004), adult sobriety (Junior, 2006), spirituality among HIV-positive patients (Litwinczuk & Groh, 2007), and even quality in life among patients with rheumatoid arthritis (Verduin, 2008).…”
Section: Purpose In Life (P Il) Testmentioning
confidence: 99%
“…Nicholson, et al ( 1994 ), in an early study using the LAP-R, investigated the differences of meaning in life between 49 drug abuse patients and a control group of 49 subjects. Multivariate analysis resulted in findings indicating significant differences in the mean scores between the two groups for the LAP-R constructs of the Personal Meaning Index functioning (.26 and .27, respectively), and vitality (.29 and .57, respectively).…”
Section: Life-span and Gerontology Studies Research In The Field Ofmentioning
confidence: 99%